Risk factors and long-term outcomes after tetralogy of Fallot repair at an Asian tertiary referral center. (May 2022) - Chungsomprasong, Paweena; Somkittithum, Pimonrat; Chanthong, Prakul; Vijarnsorn, Chodchanok; Durongpisitkul, Kritvikrom; Soongswang, Jarupim; Subtaweesin, Thaworn; Sriyodchartti, Somchai
Background: Tetralogy of Fallot is the most common type of cyanotic congenital heart disease. More postoperative tetralogy of Fallot patients grow up than in the past, and these patients need to be followed-up. Objective: To investigate the survival and long-term outcomes of patients who underwent total repair of tetralogy of Fallot, and to identify the risk factors for reoperation with pulmonic valve replacement. Method: A total of 403 patients who underwent total tetralogy of Fallot repair at our center during 1997 to 2016 were retrospectively included. Demographic, clinical, treatment, outcome, and follow-up data were collected and analyzed. Results: Median age and body weight at the time of tetralogy of Fallot repair was 4.41 years (range: 0.85–55.28) and 13.58 kg (range: 5.5–68), respectively. The median follow-up was 9.0 years, and overall mortality was 3.2%. The actuarial survival rates at 10 and 20 years were 96.4% and 95.2%, respectively, and the freedom from pulmonic valve replacement was 93.4% and 57.4%, respectively. The median time to indicate pulmonic valve replacement was 13.9 years (range: 6.2–20.5). Multivariate analysis revealed transannular patch technique (hazard ratio: 3.023, 95% confidence interval: 1.34–6.83; p  = 0.008) and palliative shunt (hazard ratio: 2.39, 95% confidence interval: 1.16–4.91; p  = 0.018) to be independent risk factors for reoperation with pulmonic valve replacement. Conclusion: The rates of overall survival and freedom from pulmonic valve replacement were both high in this study, and both were comparable to the rates reported from other studies. Overall mortality was as low as 3.47%. The need for a transannular patch or palliative shunt should be considered risk factors for a consequent reoperation.